THE EFFECT OF INTERACTIVE DIGITAL MEDIA AND LEARNING MOTIVATION ON SOCIAL SCIENCE LEARNING OUTCOMES - nurdin; Onik Farida Ni’matullah; Rusno (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research is motivated by the low self-confidence of teachers in using interactive digital media which impacts on low motivation and learning outcomes of students in social studies. This study aims to determine the effect of interactive digital media and learning motivation on the learning outcomes of eighth grade students of SMPN 7 Buton, both simultaneously and partially. The study used a quantitative associative explanatory design approach. The research subjects were 147 students in grades VII and VIII. Data were collected through observation, interviews, documentation, and closed questionnaires to measure the level of motivation and understanding of interactive media. Data analysis used multiple linear regression and supported by qualitative analysis from the interview results. The results showed that interactive digital media and learning motivation had a positive and significant effect on student learning outcomes, evidenced by the acquisition of a media coefficient value of 0.342 and motivation of 0.415. The t-test results showed a value of 8.143 for media and 9.222 for motivation with a significance level of 0.00 < 0.05. Thus, this study proves that the use of interactive digital media and learning motivation have a positive and significant effect on improving student learning outcomes. This is in line with the demands of 21st-century learning which emphasizes the use of technology, strengthening critical thinking skills, creativity, communication, and collaboration in learning.